Protestant religious leaders’ role in supporting reduce-reuse-recycle community practices in Kupang City - Riska Novatsiani Pa Padja; Iswanto; Supriyati (Universitas Gadjah Mada, 2021)
Purpose: Local leaders become the potential stakeholders who can encourage and increase community participation. This study was aimed to explore the role of the Protestant religious leaders in Kupang City in supporting 3R-based waste management. Method: This was a mixed-method study. Quantitative data related to knowledge, attitudes, 3R-based waste management practices, and the role of religious leaders in supporting waste management efforts were obtained from 271 religious leaders using a structured questionnaire. In addition, quantitative data collection regarding community compliance was obtained from 229 congregations through an online survey. While the qualitative data to assess the self-efficacy of religious leaders in mobilizing community participation was done through in-depth interviews. Results: Most of the religious leaders (42,1%) had a good level of knowledge about 3R-based waste management, but their attitudes (36,5%) and waste management practices (43,2%) were moderate. Besides, most of the congregation (40,4%) had moderate compliance with religious leaders. Religious leaders collaborated with various stakeholders to improve community participation in the 3R-based waste management. In addition, religious leaders had high self-efficacy for empowering communities on the 3R-based waste management. Conclusion: Religious leaders had a potential role in empowering the community on the program 3R-based waste management. Therefore, health providers need to engage religious leaders to support the health program, especially waste management.